Insights into the Pharmacological Effects of Soy Isoflavones on Catecholamine System - Yanagihara, Nobuyuki; Toyohira, Yumiko; Liu, Minhui; Ueno, Susumu; Tsutsui, Masato; Zhang, Han (IntechOpen, 2011)
None